2020
DOI: 10.2991/artres.k.201102.002
|View full text |Cite
|
Sign up to set email alerts
|

High Systolic Blood Pressure is Associated with Increased Cardio-ankle Vascular Index in the Elderly

Abstract: Background: Increased arterial stiffness caused by elevated Blood Pressure (BP) can be indicated by the Cardio-ankle Vascular Index (CAVI). However, the relationship between arterial stiffness and BP is complex. In addition, changes in BP may contribute to increased risk of cardiovascular disease associated with abnormal lipid profiles. So far, results from published studies have been inconclusive. Objectives:To evaluate lipid profiles and BP, and their association with CAVI values in elderly participants. Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 36 publications
(48 reference statements)
0
1
0
Order By: Relevance
“…However, CAVI was reported to be signi cantly, but more weakly than baPWV, correlated with blood pressure in subjects receiving routine health checkups [23]. Moreover, a cross-sectional study in elderly individuals indicated that systolic blood pressure in high-CAVI group (CAVI ≥ 9) patients correlated signi cantly with CAVI, whereas blood pressure in the low-CAVI (CAVI < 9) group patients showed no signi cant associations with CAVI [29]. The results of these and our studies allow us to conclude that the CAVI, as well as baPWV, might be in uenced by blood pressure.…”
Section: Discussionmentioning
confidence: 98%
“…However, CAVI was reported to be signi cantly, but more weakly than baPWV, correlated with blood pressure in subjects receiving routine health checkups [23]. Moreover, a cross-sectional study in elderly individuals indicated that systolic blood pressure in high-CAVI group (CAVI ≥ 9) patients correlated signi cantly with CAVI, whereas blood pressure in the low-CAVI (CAVI < 9) group patients showed no signi cant associations with CAVI [29]. The results of these and our studies allow us to conclude that the CAVI, as well as baPWV, might be in uenced by blood pressure.…”
Section: Discussionmentioning
confidence: 98%